Niat Berperilaku Masyarakat dalam Menggunakan Vaksin halal : Penerapan Teori of Planned Behaviour - Haifah Nabilatul Azizah; Purwanto Purwanto; Achmad Nur Alfianto; Achmad Labib (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
Vaccines have an important influence in overcoming the covid-19 virus outbreak, the higher public doubts about the covid-19 vaccine can affect people's intentions to use the covid-19 vaccine. The purpose of this study is to find out how the Theory Planned of Behavior is applied in predicting people's behaviour to use the covid-19 vaccine with subjective norms focused on the media. This study collects data through an online survey by distributing questionnaires from Google Form. The sample was taken as many as 154 people of Magelang district aged 16-40 years had been selected based on purposive sampling technique. Data analysis using SEM-PLS. The results of this study show that of the three variables, namely attitudes, subjective norms and perceived behavior control, only the attitude variable has a significant influence on the intention to use the covid-19 vaccine.